2016
DOI: 10.1176/appi.ps.201600271
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Open Dialogue for Early-Onset Psychosis Into the U.S. Health Care Environment: A Feasibility Study

Abstract: Open Dialogue (OD) is a Finnish approach to crisis intervention and ongoing care for young people experiencing psychosis and other psychiatric crises. OD engages the individual and family (or other supports) in meetings, with open discussions of all aspects of the clinical situation, and in decision making. Although psychiatric assessment and treatment occur, the initial emphasis is on engagement, crisis intervention, and promoting dialogue. Finnish studies are encouraging, with excellent clinical and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 8 publications
1
53
0
6
Order By: Relevance
“…Due to its potential as an alternative approach to mental health care, there has been increasing interest in Open Dialogue outside Finland. Over the last two decades, Open Dialogue has been introduced in health care services across Scandinavia, the United Kingdom, Italy, Germany, and the United States (for examples see Brottveit, ; Buus et al, ; Gordon et al, ; Holmesland, ; Razzaque & Wood, ; Rosen & Stoklosa, ). As Open Dialogue expands to settings outside of Finland, there is a need for contextually specific local adaptions of the approach and a need to understand successful implementation strategies, including Australian applications.…”
Section: Faq 1 Don't We Do This Already?mentioning
confidence: 99%
“…Due to its potential as an alternative approach to mental health care, there has been increasing interest in Open Dialogue outside Finland. Over the last two decades, Open Dialogue has been introduced in health care services across Scandinavia, the United Kingdom, Italy, Germany, and the United States (for examples see Brottveit, ; Buus et al, ; Gordon et al, ; Holmesland, ; Razzaque & Wood, ; Rosen & Stoklosa, ). As Open Dialogue expands to settings outside of Finland, there is a need for contextually specific local adaptions of the approach and a need to understand successful implementation strategies, including Australian applications.…”
Section: Faq 1 Don't We Do This Already?mentioning
confidence: 99%
“…Outcome studies on both OD (Seikkula et al, 2006;Gordon et al, 2016) and NAA (Lehtinen et al, 2000) indicate that with low-threshold-and integrative family-oriented treatment of first-episode psychosis, the total recovery rates are often better than those with treatment-as-usual. For example, two-and five-year non-randomized follow-up studies conducted in Western Lapland showed that with OD there is a decrease in both the overall need for psychiatric treatment and the incidence of residual psychotic symptoms (Seikkula et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The Open Dialogue approach has continued to be adapted as it has been introduced to sites outside of Finland. Open Dialogue now has a presence across various international settings, including Norway, Denmark, the United States, UK, Italy, Germany (Gordon et al 2016;Rosen & Stoklosa 2016), and more recently Australia. In these settings, it has undergone local adaptations as proponents of Open Dialogue attempt to implement the approach in new and varied social and political contexts.…”
Section: International Adaptations Of Open Dialoguementioning
confidence: 99%
“…In these settings, it has undergone local adaptations as proponents of Open Dialogue attempt to implement the approach in new and varied social and political contexts. Implementation of Open Dialogue outside of Finland is impacted by various contextbound facilitators and barriers, such as staff training, diverse organizational models and service structures, the resourcing of mental health services, and localized translation of the principles of Open Dialogue (Buus et al 2017;Gordon et al 2016;Rosen & Stoklosa 2016).…”
Section: International Adaptations Of Open Dialoguementioning
confidence: 99%